2014
DOI: 10.1177/0013124513514773
|View full text |Cite
|
Sign up to set email alerts
|

Service-Learning as a Catalyst for Community Development

Abstract: Service-learning has the potential to create mutually beneficial relationships between schools and communities, but little research explores service-learning from the community’s perspective. The purpose of this study was to (a) understand how community-based organizations (CBOs) benefited from partnering with students and (b) examine whether organizational capacity (e.g., organization size) or employee vision (e.g., belief in the abilities of children) had a greater impact on the extent to which organizations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 16 publications
(24 reference statements)
0
16
0
3
Order By: Relevance
“…In their survey of empirical research on service learning, Eyler, Giles, and Gray (1999) reported only eight studies that investigated community impacts in service learning. Subsequent research has largely focused on satisfaction with the service learning program (Ferrari & Worrall, 2000;Gelmon, 2003;Schachter & Schwartz, 2009), building capacity of the community-based organizations (e.g., strengthening networks, improving fund-raising; Budhai, 2013;Carpenter & Krist, 2011;Geller, Zuckerman & Seidel, 2016;Olberding & Hacker, 2016), strengthening town-gown relationships (Sandy & Holland, 2006), utilizing free labor and knowledge of college students and other university resources (Budhai, 2013;Carpenter & Krist, 2011;Edwards, Mooney & Heald, 2001;Olberding & Hacker, 2016;Worrall, 2007), and improved client service (Geller, Zuckerman & Seidel, 2016;Gray, et al, 2000).…”
Section: Prior Researchmentioning
confidence: 99%
“…In their survey of empirical research on service learning, Eyler, Giles, and Gray (1999) reported only eight studies that investigated community impacts in service learning. Subsequent research has largely focused on satisfaction with the service learning program (Ferrari & Worrall, 2000;Gelmon, 2003;Schachter & Schwartz, 2009), building capacity of the community-based organizations (e.g., strengthening networks, improving fund-raising; Budhai, 2013;Carpenter & Krist, 2011;Geller, Zuckerman & Seidel, 2016;Olberding & Hacker, 2016), strengthening town-gown relationships (Sandy & Holland, 2006), utilizing free labor and knowledge of college students and other university resources (Budhai, 2013;Carpenter & Krist, 2011;Edwards, Mooney & Heald, 2001;Olberding & Hacker, 2016;Worrall, 2007), and improved client service (Geller, Zuckerman & Seidel, 2016;Gray, et al, 2000).…”
Section: Prior Researchmentioning
confidence: 99%
“…It can help students better understand the concepts discussed in class through direct exposure to issues and strengths in the community (Burnett, Long, & Horn, 2005). Integrating service-learning programs into curricula can also be beneficial for communities (Geller, Zuckerman, & Seidel, 2016). In counseling programs, such assignments can expose students to diverse environments and provide them with structured experiences for multicultural growth and development (Baggerly, 2006), and may also help to promote counselor competencies in advocating for clients against societal and systemic barriers (Murray, Pope & Powell, 2010).…”
Section: Service-learning and Counselor Educationmentioning
confidence: 99%
“…Cultural humility, including the ability to engage with and interact with various ethnic and cultural groups (Budhai, 2013;Chupp & Joseph, 2010;Sabo et al, 2015) Career development Deeper investments in community engaged scholarship and "real-world" public health research (Comeau et al, 2019;Olberding & Hacker, 2016;Sabo et al, 2015) University Faculty Extends research agenda, brings relevance to research, and facilitates impact from research (outputs and outcomes for communities and/or for scholarship) (Chupp & Joseph, 2010;Comeau et al, 2019;Olberding & Hacker, 2016) University profile Improved university image, reputation, and brand Chupp & Joseph, 2010;Comeau et al, 2018;Olberding & Hacker, 2016) Community relations Collective problem-solving (Gerstenblatt, 2014) Quality of life Can help with recruiting and retaining students, faculty, and staff (Olberding & Hacker, 2016) Community Organizational capacity + reach Expanded labor force, increased service provision, greater ability to serve clients, greater capacity to take on new projects, enhanced services, improved client outcomes due to student outputs, including reports, conference presentations, community/needs assessments, data collection, data analysis, provision of quality data and reports, strategic program design, proposal/grant writing, use of processes for community-centered decision-making, and meeting/workshop planning/ facilitation (Budhai, 2013;Chupp & Joseph, 2010;Comeau et al, 2019;Driscoll et al, 1996;Edwards et al, 2001;Geller et al, 2016;Gerstenblatt, 2014;James & Logan, 2016;Olberding & Hacker, 2016;Sabo et al, 2015;Worrall, 2007) Organizational/ staff/ volunteer knowledge + skills Advocacy, teaching techniques, improved presentation skills, patience, personal and collective problem-solving, resilience, digital technology, computer literacy, respect for intra-professionalism, and civic mindedness, helping inform tool/process development or refinement, improving volunteer management, fundraising, strategies, infrastructure and systems (Gerstenblatt, 2014;…”
Section: Studentmentioning
confidence: 99%